Serum Level Changes of Neurotrophin-3 after Performing Diabetic Foot Exercise in Diabetic Neuropathy - Tri Wahyuliati; Agung Pranoto; Samekto Wibowo (International Journal of Public Health Science (IJPHS), 2015)
The research aimed to determine the pattern of changes in serum levels of NT-3 in the improvement of diabetic neuropathy, after doing diabetic foot exercise. A true experimental study with randomaized pre – post test control trial. A total of 36 subjects meeting the inclusion and exclusion criteria were included in the exercise group or the control one with age matched systematic random sampling method. Exercise group had a significant improvement on the score of ABI (p.0.002), systolic blood pressure (p.0.014), diastolic blood pressure (p.0.055), DNS (p.0.01), DNE (p.0.001) and increased of serum level of NT-3 (p.0.049). Control group had result respectively on ABI (p.0.131), systolic blood pressure (p.0.668), diastolic blood pressure (p.0.216), DNS (p.1.00), DNE (p.0.543), and increase of NT-3 (p.0.264). The comparation results of the two groups had a significant different on the score of ABI (p.0.01), systolic blood pressure (p.0.01), diastolic blood pressure (p.0.01), DNS (p.0.01), DNE (p.0.01), and increased of NT-3 (p.0.01). Diabetic foot exercise had a peripheral affect on a clinically significant improvement based on ABI scores, systolic and diastolic blood pressure, DNS and DNE, and increase of serum level of NT-3.